Application of stem cell for the regeneration of spiral ganglion neurons - Mohammadian, F.; Eatemadi, A.; Daraee, H. (Cellular and Molecular Biology, 2017)
Over 278 million of people worldwide suffers from hearing loss, and this disease has significant detrimental effects emotionally and economically on individuals and the society in totality. Treatment using cochlear implant dramatically improve the perception, and production of speech, as well as the patient quality of life, with the different sensorineural hearing loss (SNHL). Yet, there are some challenges faced by a cochlear implant. In this review, we propose the regeneration of spiral ganglion neurons which is an interface neuron using human amniotic fluid mesenchymal stem cells (hAFMSCs), due to its high pluripotency potentials, this stem cell source can regenerate the spiral ganglion and this in-turn will bring back the inner ear hair-cells to functionality.